Genome-Wide Identification and Analysis of the SBP-Box Family Genes under Phytophthora capsici Stress in Pepper (Capsicum annuum L.) - Zhang, Huai-Xia; Jin, Jing-Hao; He, Yu-Mei; Lu, Bo-Ya; Li, Da-Wei; Chai, Wei-Guo; Khan, Abid; Gong, Zhen-Hui (Frontiers in Plant Science, 2016)
SQUAMOSA promoter binding protein (SBP)-box genes encode plant-specific transcription factors that are extensively involved in many physiological and biochemical processes, including growth, development, and signal transduction. However, pepper (Capsicum annuum L.) SBP-box family genes have not been well characterized. We investigated SBP-box family genes in the pepper genome and characterized these genes across both compatible and incompatible strain of Phytophthora capsici, and also under different hormone treatments. The results indicated that total 15 members were identified and distributed on seven chromosomes of pepper. Phylogenetic analysis showed that SBP-box genes of pepper can be classified into six groups. In addition, duplication analysis within pepper genome, as well as between pepper and Arabidopsis genomes demonstrated that there are four pairs of homology of SBP-box genes in the pepper genome and 10 pairs between pepper and Arabidopsis genomes. Tissue-specific expression analysis of the CaSBP genes demonstrated their diverse spatiotemporal expression patterns. The expression profiles were similarly analyzed following exposure to P. capsici inoculation and hormone treatments. It was shown that nine of the CaSBP genes (CaSBP01, 02, 03, 04, 05, 06, 11, 12, and 13) exhibited a dramatic up-regulation after compatible HX-9 strain (P. capsici) inoculation, while CaSBP09 and CaSBP15 were down-regulated. In case of PC strain (P. capsici) infection six of the CaSBP genes (CaSBP02, 05, 06, 11, 12, and 13) were arose while CaSBP14 was down regulated. Furthermore, Salicylic acid, Methyl jasmonate and their biosynthesis inhibitors treatment indicated that some of the CaSBP genes are potentially involved in these hormone regulation pathways. This genome-wide identification, as well as characterization of evolutionary relationships and expression profiles of the pepper CaSBP genes, will help to improve pepper stress tolerance in the future.